High Adenosine Deaminase Level and Erythrocyte Sedimentation Rate of Intestinal Tuberculosis Patients - Nuri Dyah Indrasari; Marcellus Simadibrata; Primariadewi Rustamadji; Yusra Yusra; Aria Kekalih; Suhendro Suhendro; Alida Roswita Harahap; Heri Wibowo; Ida Parwati; Ferry Sandra (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: Currently, laboratory diagnosis of intestinal tuberculosis (ITB) is limited based on clinical manifestations, providing opportunities for alternative laboratory tests to diagnose ITB. At the present time, the role of serum adenosine deaminase (ADA) and hematological tests in ITB patients are not widely known. The objective of this study was to determine the role of ADA and hematological tests in patients suspected with ITB.METHODS: Subjects that were suspected of ITB were classified as ITB group, while subjects with inflammatory bowel disease, hemorrhoid, and intestinal malignancy were classified as non-ITB group. Colonoscopy, histopathological examinations, and hematological test were performed. ADA measurement was also performed with clinical chemistry analyzer based on enzymatic colorimetry principle.RESULTS: Out of 143 subjects, 16 (11.2%) subjects were diagnosed with ITB and 127 (88.8%) subjects were classified as non-ITB group. ADA level and erythrocyte sedimentation rate (ESR) of ITB group were significantly higher than the ones of non-ITB group (p<0.05). Cut-off, sensitivity, and specificity of ADA level were 12.56 IU/L, 75%, and 57%, respectively. Cut-off, sensitivity, and specificity of ESR were 32.5 mm/hour, 81%, and 62%, respectively. Colonoscopy of ITB subjects displayed multiple ulcerations, edema, and hyperemic mucosa. Histopathological examination of ITB subjects exhibited granulomatous inflammation, epitheloid cells, giant cells, and lymphocyte aggregates.CONCLUSION: ADA level and ESR were significantly higher among ITB patients compared with non-ITB patients. Since the sensitivities of ADA and ESR tests were high, the ADA and ESR tests could be considered as a screening test for ITB.KEYWORDS: intestinal tuberculosis, adenosine deaminase, hematological tests